Effectiveness of a Barcode Medication Administration System in Reducing Preventable Adverse Drug Events in a Neonatal Intensive Care Unit: A Prospective Cohort Study - Morriss, Frank H.; Abramowitz, Paul W.; Nelson, Steven P.; Milavetz, Gary; Michael, Stacy L.; Gordon, Sara N.; Pendergast, Jane F.; Cook, E. Francis (The Journal of pediatrics, 2009)
Patients are at risk of harm from medication errors. Barcode medication administration (BCMA) systems are recommended to mitigate preventable adverse drug events (ADEs). Our hypothesis was that a BCMA system would reduce preventable ADEs by 45% in a neonatal intensive care unit. We conducted a prospective, observational, cohort study of a BCMA system intervention in a neonatal intensive care unit. Participants were admitted neonates during 50 weeks. Medication errors and potential or preventable ADEs were detected by a daily structured audit of each subject's medical record, with assignment of an event as a preventable ADE made by blinded assessors. The generalized estimating equation method was used in modeling the targeted, preventable ADE rate with covariates. A total of 92 398 medication doses were administered to 958 subjects. The generalized estimating equation method yielded a relative risk of preventable ADE when the system was implemented of 0.53 (95% confidence limits 0.29 to 0.91, P = .04), adjusted for log10doses of medication/subject/day, a significant predictive covariate (P < .001), as well as for birth weight, sex, Caucasian race, birth cohort number, and nursing hours/subject/day. The BCMA system reduced the risk of targeted, preventable ADEs by 47%, controlling for the number of medication doses/subject/day, an important risk exposure.